2020
DOI: 10.1136/annrheumdis-2020-eular.2037
|View full text |Cite
|
Sign up to set email alerts
|

Ab0448 impact of Remission on Damage Accrual in Systemic Lupus Erythematosus (Sle) Patients: A Systematic Literature Review (Slr)

Abstract: Background:Treat-to-target strategy with remission as the target has been proposed for the management of SLE. However, there is not a uniform definition of remission.Objectives:To determine the protective value of remission state on organ damage accrual in SLE patients through a SLR.Methods:Two independent reviewers identified studies in Medline and Cochrane Library. Data on remission definitions and rates as well as damage accrual (assessed by the SLICC/ACR damage index [SDI]) were extracted. Definitions of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The full results of the SLR on the influence of remission on health-related quality of life (HR-QoL) and on damage have been presented 5 and will be published elsewhere. Three studies investigated the association between being or staying in remission (by any definition) and HR-QoL and concluded that remission by any definition was associated with better HR-QoL.…”
Section: Slr On the Influence Of Remission On Health-related Quality Of Life And On Damagementioning
confidence: 99%
“…The full results of the SLR on the influence of remission on health-related quality of life (HR-QoL) and on damage have been presented 5 and will be published elsewhere. Three studies investigated the association between being or staying in remission (by any definition) and HR-QoL and concluded that remission by any definition was associated with better HR-QoL.…”
Section: Slr On the Influence Of Remission On Health-related Quality Of Life And On Damagementioning
confidence: 99%
“…According to these data, remission could be an achievable state in many patients, and it should remain as the ideal target in SLE treatment. However, as more stringent definitions (remission off-and on-treatment) are less frequently achieved in patients with a higher risk of poorer outcomes (like non-White populations or with more severe manifestations), less stringent definitions could be more realistic outcomes for the treatment of SLE patients (2,(41)(42)(43). For example, EULAR and PANLAR guidelines recommended remission or LDA as the therapeutic goal (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Remission and low disease activity (LDA) have been proposed as targets for the management of systemic lupus erythematosus (SLE) (1). These states have been associated with a lower probability of mortality, damage, flares, hospitalization, costs, cardiovascular events and with a better health-related quality of life (HRQoL) (2). However, there are various definitions of these states.…”
Section: Introductionmentioning
confidence: 99%
“…In the wake of the principle of treating-to-target (T2T) in rheumatoid arthritis, remission and LDAS have been proposed as desirable therapeutic goals for patients with SLE (2,21,41). Emerging studies have demonstrated that the attainment of remission/LDAS was associated with improved outcomes in SLE, including lower damage accrual, lower probability of flares, and a better HRQoL (42). Regarding HRQoL, being on remission/LDAS was reported to predict higher scores in the components of physical health, but not in the components of mental health (16,18,42).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have demonstrated that the attainment of remission/LDAS was associated with improved outcomes in SLE, including lower damage accrual, lower probability of flares, and a better HRQoL (42). Regarding HRQoL, being on remission/LDAS was reported to predict higher scores in the components of physical health, but not in the components of mental health (16,18,42). The data from our study also indicated a lack of associations between remission/LDAS and SWB, probably because the mental domains are influenced by more complicated factors such as demographic characteristics, personality, and culture except for SLE-related factors involved in the definition of remission/LDAS at present.…”
Section: Discussionmentioning
confidence: 99%